Structural Changes of the Nail Plate after Repeated Application of Gel and Acrylic Coatings: An Analysis of Current Evidence - Dorobaliuk, Tetiana (Global Prosperity, 2022)
Abstract. Over the past decade, gel and acrylic nail coatings have become a widespread cosmetic practice; however, their impact on the structure of the nail plate when repeatedly applied remains a subject of debate in dermatology and cosmetology. The aim of this study is to provide a systematic analysis of published data on morphological, biochemical, and biomechanical changes of the nail plate following multiple cycles of application and removal of gel and acrylic systems. The literature review covers studies published between 2016 and 2022, including clinical observations, instrumental examinations, and biochemical analyses. The findings indicate that repeated procedures lead to a reduction in nail plate thickness, decreased hydration, disruption of the lipid barrier, and alterations in the mechanical properties of keratin. The most pronounced damage occurs when aggressive surface preparation and removal methods are used. Three-dimensional scanning reveals topographical changes in the nail surface that correlate with the frequency of procedures. Acid primers and acetone-containing solvents cause delamination and increased porosity. Preventive measures include the use of gentle preparation systems, non-abrasive removal methods, adherence to recovery intervals, and the application of keratin-containing products. The results highlight the need to develop scientifically grounded protocols for aesthetic procedures in order to minimize damage to the nail plate.